The Implementation of Teachers’ Emotional Intelligence in Enhancing the Success of Akidah Akhlak Instruction at MIS Al-Khairaat Pombewe - Diajeng Yuliana Putri; Askar Askar; Darmawansyah Darmawansyah (FKIP - Universitas Riau, 2026)
Islamic education aims to develop individuals who are intellectually, emotionally, and spiritually balanced. Therefore, education is not only directed toward mastering knowledge but also toward fostering moral values and character. This study aims to analyze the implementation of teachers’ emotional intelligence in improving the success of Akidah Akhlak learning at MIS Al-Khairaat Pombewe. The research employed a qualitative approach with a descriptive design. The participants included the school principal, Akidah Akhlak teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. The findings reveal that teachers’ emotional intelligence is reflected in their ability to manage emotions, show empathy, and build positive communication with students. Teachers function not only as instructors but also as role models and moral guides. The success of learning can be observed in students’ cognitive, affective, and psychomotor development. Students demonstrate an understanding of Akidah Akhlak concepts, respect for teachers, empathy toward peers, and ethical behavior in daily life. Supporting factors include family support, the religious culture of the madrasah, and teachers’ awareness of the importance of emotional connections. However, challenges arise from students’ diverse personalities, family backgrounds, and teachers’ limitations in emotional regulation. The study concludes that teachers’ emotional intelligence plays a significant role in learning success and students’ character development.